Understanding the role of active site residues in CotB2 catalysis using a cluster model - Raz, Keren; Driller, Ronja; Brück, Thomas; Loll, Bernhard; Major, Dan T. (Beilstein Journal of Organic Chemistry, 2020)
Terpene cyclases are responsible for the initial cyclization cascade in the multistep synthesis of a large number of terpenes. CotB2 is a diterpene cyclase from Streptomyces melanosporofaciens, which catalyzes the formation of cycloocta-9-en-7-ol, a precursor to the next-generation anti-inflammatory drug cyclooctatin. In this work, we present evidence for the significant role of the active site's residues in CotB2 on the reaction energetics using quantum mechanical calculations in an active site cluster model. The results revealed the significant effect of the active site residues on the relative electronic energy of the intermediates and transition state structures with respect to gas phase data. A detailed understanding of the role of the enzyme environment on the CotB2 reaction cascade can provide important information towards a biosynthetic strategy for cyclooctatin and the biomanufacturing of related terpene structures.
Keywords: active site; CotB2 cyclase; diterpene; mechanism; quantum mechanics

(untitled) - Knowles, J. R. (Nature, 1991)

(untitled) - Warshel, A. (Proc. Natl. Acad. Sci. U. S. A., 1978)

(untitled) - Christianson, D. W. (Chem. Rev., 2017)

(untitled) - Devappa, R. K.; Makkar, H. P. S.; Becker, K. (J. Am. Oil Chem. Soc., 2011)

(untitled) - Singh, B.; Sharma, R. A. (3 Biotech, 2015)

(untitled) - Schwab, W.; Davidovich-Rikanati, R.; Lewinsohn, E. (Plant J., 2008)

Medicinal Natural Products: A Biosynthetic Approach - Dewick, P. M. (John Wiley & Sons, 2001)

(untitled) - Radhakrishna, S.; Kumari, P. S. (Adv. Appl. Sci. Res., 2018)

(untitled) - Rates, S. M. K. (Toxicon, 2001)

(untitled) - Gershenzon, J.; Dudareva, N. (Nat. Chem. Biol., 2007)

(untitled) - Gonzalez-Burgos, E.; Gomez-Serranillos, M. P. (Curr. Med. Chem., 2012)

Taxane Anticancer Agents - Basic Science and Current Status - Croteau, R.; Hezari, M.; Hefner, J.; Koepp, A.; Lewis, N. G. (Paclitaxel Biosynthesis - The Early Steps, 1994)

(untitled) - Cane, D. E. (Chem. Rev., 1990)

(untitled) - Christianson, D. W. (Chem. Rev., 2006)

(untitled) - Tholl, D. (Curr. Opin. Plant Biol., 2006)

(untitled) - Zwenger, S.; Basu, C. (Biotechnol. Mol. Biol. Rev., 2008)

(untitled) - Janke, R.; Görner, C.; Hirte, M.; Brück, T.; Loll, B. (Acta Crystallogr., Sect. D: Biol. Crystallogr., 2014)

(untitled) - Whittington, D. A.; Wise, M. L.; Urbansky, M.; Coates, R. M.; Croteau, R. B.; Christianson, D. W. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Lesburg, C. A.; Zhai, G.; Cane, D. E.; Christianson, D. W. (Science, 1997)

(untitled) - Starks, C. M.; Back, K.; Chappell, J.; Noel, J. P. (Science, 1997)

(untitled) - Wendt, K. U.; Poralla, K.; Schulz, G. E. (Science, 1997)

(untitled) - Köksal, M.; Jin, Y.; Coates, R. M.; Croteau, R.; Christianson, D. W. (Nature, 2011)

(untitled) - Croteau, R. (Chem. Rev., 1987)

(untitled) - Brück, T.; Kourist, R.; Loll, B. (ChemCatChem, 2014)

(untitled) - Tantillo, D. J. (Nat. Prod. Rep., 2011)

(untitled) - Hess, B. A., Jr; Smentek, L.; Noel, J. P.; O’Maille, P. E. (J. Am. Chem. Soc., 2011)

(untitled) - Tantillo, D. J. (Angew. Chem., Int. Ed., 2017)

(untitled) - Dixit, M.; Weitman, M.; Gao, J.; Major, D. T. (ACS Catal., 2017)

(untitled) - Weitman, M.; Major, D. T. (J. Am. Chem. Soc., 2010)

(untitled) - Major, D. T.; Weitman, M. (J. Am. Chem. Soc., 2012)

(untitled) - Gao, J.; Ma, S.; Major, D. T.; Nam, K.; Pu, J.; Truhlar, D. G. (Chem. Rev., 2006)

(untitled) - Major, D. T.; Freud, Y.; Weitman, M. (Curr. Opin. Chem. Biol., 2014)

(untitled) - Ansbacher, T.; Freud, Y.; Major, D. T. (Biochemistry, 2018)

(untitled) - Dixit, M.; Weitman, M.; Gao, J.; Major, D. T. (ACS Catal., 2017)

(untitled) - Freud, Y.; Ansbacher, T.; Major, D. T. (ACS Catal., 2017)

(untitled) - Major, D. T. (ACS Catal., 2017)

(untitled) - Newman, D. J.; Cragg, G. M. (J. Nat. Prod., 2016)

(untitled) - Hong, Y. J.; Tantillo, D. J. (Org. Biomol. Chem., 2015)

(untitled) - Sato, H.; Teramoto, K.; Masumoto, Y.; Tezuka, N.; Sakai, K.; Ueda, S.; Totsuka, Y.; Shinada, T.; Nishiyama, M.; Wang, C.; Kuzuyama, T.; Uchiyama, M. (Sci. Rep., 2015)

(untitled) - Kim, S.-Y.; Zhao, P.; Igarashi, M.; Sawa, R.; Tomita, T.; Nishiyama, M.; Kuzuyama, T. (Chem. Biol., 2009)

(untitled) - Meguro, A.; Motoyoshi, Y.; Teramoto, K.; Ueda, S.; Totsuka, Y.; Ando, Y.; Tomita, T.; Kim, S.-Y.; Kimura, T.; Igarashi, M.; Sawa, R.; Shinada, T.; et al. (Angew. Chem., Int. Ed., 2015)

(untitled) - Driller, R.; Janke, S.; Fuchs, M.; Warner, E.; Mhashal, A. R.; Major, D. T.; Christmann, M.; Brück, T.; Loll, B. (Nat. Commun., 2018)

(untitled) - Tantillo, D. J.; Jiangang, C.; Houk, K. N. (Curr. Opin. Chem. Biol., 1998)

(untitled) - Siegbahn, P. E. M.; Himo, F. (Wiley Interdiscip. Rev.: Comput. Mol. Sci., 2011)

(untitled) - Grimme, S.; Steinmetz, M. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Mati, I. K.; Cockroft, S. L. (Chem. Soc. Rev., 2010)

Gaussian 16, Revision A. 03 (Gaussian, Inc., 2016)

(untitled) - Zhao, Y.; Truhlar, D. G. (Theor. Chem. Acc., 2008)